Pemberdayaan Kelompok Peternak Sapi Pedaging Melalui Pelatihan Produksi Kompos - Said, Muhammad Irfan; Utamy, Renny Fatmyah; Amran, Amran (Insan Kreasi Media, 2022)
Utilization of livestock waste is one of the efforts to reduce the environmental burden. Feces produced by beef cattle farming has a very large potential to be processed into compost. Compost has a very high economic value if it can be developed professionally. Efforts to treat waste commercially require sufficient technological knowledge. One of the efforts to increase technological knowledge for farmers is through training. The purpose of this activity is to increase the knowledge of farmer group partners regarding the process of processing beef cattle waste into compost. This activity was carried out in Kalase'rena Sub District, Bontonompo District, Gowa Regency. The partner involved is the farmer-livestock group “Ballaparang”. The method of implementing technology applied activities is carried out through training activities (face to face) which are then followed by practical implementation. To deepen the training process, then a technology demonstration plot was made as a pilot project. The results of the activity show that this training activity has a very real impact in increasing knowledge capacity in processing and utilizing beef cattle waste as the main ingredient in the compost production process.